2022
DOI: 10.3390/ijerph191710724
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern and Influencing Factors of Heavy Metal Resistance Genes in the Yellow River Sediments of Henan Section

Abstract: The transformation of heavy metal resistance genes (MRGs) in the environment has attracted increasing attention in recent years. However, few studies have reported the MRG content in the Yellow River, one of the main irrigation water sources in the North China Plain. In this study, we quantified MRG abundance by a metagenomic approach, and assessed the influence on MRGs of both bioavailable and total heavy metal (HM) content. The results indicate that Cu-resistant genes are the most common genes, and the preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…For example, three OTUs associated with Comamonadaceae showed positive relationships with the bioavailable Fe, Cr, and Ni. Members of Comamonadaceae have been identified as Fe(III)-reducing bacteria, which could adapt to the detrimental environment by changing their metabolic ways Zhang et al, 2022a). Consistently, two OTUs associated with Rhodocyclaceae showed positive relationships with the bioavailable Fe and Cr.…”
Section: Effects Of Geochemical Characteristics On Bacterial and Fung...mentioning
confidence: 87%
“…For example, three OTUs associated with Comamonadaceae showed positive relationships with the bioavailable Fe, Cr, and Ni. Members of Comamonadaceae have been identified as Fe(III)-reducing bacteria, which could adapt to the detrimental environment by changing their metabolic ways Zhang et al, 2022a). Consistently, two OTUs associated with Rhodocyclaceae showed positive relationships with the bioavailable Fe and Cr.…”
Section: Effects Of Geochemical Characteristics On Bacterial and Fung...mentioning
confidence: 87%
“…Streptomyces has been reported to have strong capabilities for cellulose and hemicellulose decomposition [ 54 ], as well as nitrogen-fixing [ 55 ] and antibiotic synthesis [ 56 ]. Vicinamibacteraceae , the first family within the sd6 Acidobacteria [ 57 ] which has been found to contain butyrogenic degradation-related genes and to prefer to utilize complex organic compounds [ 58 ], was found to be one of the most abundant microorganisms in the area surrounding our sample sites [ 59 ]. Penicillium and Aspergillus were found to play a role in straw degradation in previous 13 C-labeled straw decomposition experiments [ 22 ], and microbial physiological studies have revealed that they have cellulolytic enzymes and xylanase synthesis systems.…”
Section: Discussionmentioning
confidence: 99%